2017
DOI: 10.1177/1687814016687965
|View full text |Cite
|
Sign up to set email alerts
|

Design and experiment of a passive damping device for the multi-panel solar array

Abstract: With the space technology development, large flexible space deployable structures have been used widely. Studying on the vibration control for large flexible space deployable structures becomes very important. In this study, a novel passive vibration damping device is developed for the multi-panel sun-orientated deployable solar array. Its upper strut contains a viscous damper while the lower strut is rigid. The device is lockable and located near the solar array root hinge to increase the structural damping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…in which K denotes the rotational stiffness and C donates the rotational damping coefficient. Comparing equation (14) with equation ( 4), it illustrates that if rotational root springs and dampers are applied at the root of the solar panel, the effects of rotational stiffness K and damping C are both scared down by a coefficient 1 L 2 . Thus, if rotational type root springs and dampers are applied, to accomplish similar response with the modified root mounting method, the root rotational stiffness 3), (4), and ( 14) illustrate that the rotational and translational root mounting methods theoretically are of the same principle in essence, excepting that the effect of stiffness K and damping coefficient c are simultaneously scaled down for the rotational root mounting method.…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in which K denotes the rotational stiffness and C donates the rotational damping coefficient. Comparing equation (14) with equation ( 4), it illustrates that if rotational root springs and dampers are applied at the root of the solar panel, the effects of rotational stiffness K and damping C are both scared down by a coefficient 1 L 2 . Thus, if rotational type root springs and dampers are applied, to accomplish similar response with the modified root mounting method, the root rotational stiffness 3), (4), and ( 14) illustrate that the rotational and translational root mounting methods theoretically are of the same principle in essence, excepting that the effect of stiffness K and damping coefficient c are simultaneously scaled down for the rotational root mounting method.…”
Section: Theoretical Analysis and Discussionmentioning
confidence: 99%
“…The effectiveness of this passive method is quite limited unless massive of piezoelectric transducers are applied. 13 Kong and Huang 14 investigated a passive vibration suppression of a solar panel by a root damper, and found that a root damper with damping coefficient of 10 5 order of magnitude is needed, and the damper nearly has no effect if the vibration of solar panel is quite small.…”
Section: Introductionmentioning
confidence: 99%
“…Bose and Gorain 12 studied the vibration control of solar array with an ideal damper at the hub end, and he found out that the control force is proportional to a general nonlinear function of the vibration velocity, in which both torsional and bending modes are considered. Kong and Huang 13 designed a passive vibration damping device for solar arrays with a viscous damper to provide tilted support near the root hinge. Jia et al 14 reported a novel damping platform for large flexible overhanging structure, which is composed of spherical hinge, multi-damping rod and rigid support.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results show that this damping platform has damping effect on the motion of spacecraft and the vibration of flexible structure. Kong and Huang 13 reported a novel configuration of solar array damper for bending vibration, in which the upper strut contains a viscous damper and the lower strut is rigid. This damper is lockable and located near the solar array root hinge, increasing structural damping without reducing the base frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The main existing vibration control methods described in the literature can be classified into two types, namely passive control and active control. Passive control has major advantages including simple structure and it is easy to implement (Morozov and Lopatin, 2011; Kong and Huang, 2017). However, the passive control system, once designed and manufactured, has fixed characteristics such as stiffness and damping.…”
Section: Introductionmentioning
confidence: 99%